P569 Can thiopurines prevent crohn's disease endoscopic postoperative recurrence in at risk patients?. (30th January 2023) - Chehaider, A; Serghini, M; Labidy, A; Ben Mustapha, N; Fekih, M; Boubaker, J
Abstract: Background: Postoperative relapse (POR) of Crohn's disease (CD) is frequent in the absence of prophylactic treatment. Screening for known risk factors allows to stratify patients and consider appropriate therapy. In Tunisia, the cost-effectiveness of thiopurines makes it prescribed even when moderate or high risk of POR. The aim was to describe the efficacy of thiopurines in preventing endoscopic POR in patients at risk. Methods: We conducted a retrospective study enrolling CD patients who underwent curative ileo-caecal resection and received thiopurines to prevent POR. They all had at least one risk factor for POR knowing: smoking, fistulizing phenotype, extensive ileal resection (≥ 50 cm), previous bowel resection. The risk was moderate in the presence of one risk factor and high if at least two factors. Patients with a follow-up less than 6 months were excluded. All patients had undergone ileocoloscopy to screen for endoscopic POR wich was stratified according to the Rutgeerts score. Endoscopic POR was defined by a score ≥ i2 and was severe if score ≥i3. Results: Thirty nine patients were included with a sex ratio M/F =1.8 and a mean age of 31 years. CD was ileal and ileocolic in 92.3% and 7.7% respectively, with perineal involvement in 7.2%. The mean extent of ileal resection was 39.7±4 cm. The ileal and colonic histological margins were pathologic in 17.9% and 7.7% respectively. Risk factors for POR were distributed as follow: Active smoking (28.2%), previous bowel resection (17.9%), fistulizing phenotype (84.6%) extensive resection (35.9%). The risk was high in 51.3% and moderate in 48.7% of cases. The delay of introduction of thiopurines was on average 31.8±53 days from the restoration of digestive continuity at a mean dose of 2.3 mg/kg and ileocoloscopy was performed at a mean delay of 19.3 months. Rutgeerts' score was as follows: i0, i1, i2, i3 and i4 in 34.7%, 8.2%, 16.3%, 6.1% and 10.2% respectively. Endoscopic POR was noted in 43.6% and was severe in 21.6% of cases. The cumulative POR rate was 16% at 6 months, 52% at 12 months and 67.5% at 24 months. In univariate analysis, factors associated with endoscopic POR on thiopurines were male gender (p=0.012), laparotomy (p=0.02), the extent of ileal resection and extensive ileal resection (p=0.003). In multivariate analysis, the factors retained were male gender with an OR=11 (p= 0.024) and the extent of ileal resection with an OR=1.05 (p=0.02). Time to introduction of thiopurines, fistulising phenotype and smoking did not significantly influence the risk of POR. Conclusion: Thiopurines would be able to prevent endoscopic POR in more than half of the patients at risk. However, anti-TNF therapy should be indicated immediately in males and in cases of extended ileal resection.